Changes in Body Mass Index across Age Groups in Iranian Women: Results from the National Health Survey - Enayatollah Bakhshi; Behjat Seifi; Akbar Biglarian; Kazem Mohammad (Journal of Nutrition and Metabolism)
Background. To investigate the associations between some factors with weight gain across age groups in Iranian women. Methods. Proportional odds model was used to estimate the probability of BMI categorized as a function of education, economic index, workforce, smoking, marital status, and place of residence adjusted for age, using data from the “National Health Survey in Iran” database. It included 14176 women aged 20–69 years. Results. For all covariates, age was directly associated with overweight and obesity before 60 years of age. Among women aged 20–40 years, the rates of change in probabilities of overweight and obesity were highest. Among women, being inactive, with high economic index, married, being nonsmoker, in an urban residence, with lower educational attainment, all increased the probabilities of overweight and obesity. Conclusions. Women aged 20–40 years gained weight faster than other groups. They may need additional information and more support on how to reduce their risk for weight gain through positive health behaviors.